The Impact of Multi-Sensory Phonics Programs in Teaching English as an Additional Language - Langille, James; Green, Zoila (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2021)
Complexity of the various needs that come with English language learners (ELLs) beyond language learning (such as learning gaps, social and cultural differences, etc.) and increased numbers of English language learners in Canadian schools have led educational stakeholders to seek ways to promote reading improvement. While literature points out the relevance of systematic phonics instruction in reading and the importance of form-focused instruction (FFI) in English language learning, multi-sensory phonics programs (MSPPs) appear to be an effective reading tool that embodies them both. Although evidence on the efficacy of these programs is copious in students with learning difficulties, little is known about MSPPs in connection with English language learning. As a result, this integrative literature review explores the notable benefits of MSPPs, their connection with ELL instruction, and how successful program implementation may depend on teacher training.